2017
DOI: 10.5194/hess-21-5043-2017
|View full text |Cite
|
Sign up to set email alerts
|

Identifying, characterizing and predicting spatial patterns of lacustrine groundwater discharge

Abstract: Abstract. Lacustrine groundwater discharge (LGD) can significantly affect lake water balances and lake water quality. However, quantifying LGD and its spatial patterns is challenging because of the large spatial extent of the aquiferlake interface and pronounced spatial variability. This is the first experimental study to specifically study these largerscale patterns with sufficient spatial resolution to systematically investigate how landscape and local characteristics affect the spatial variability in LGD. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…There are several studies reporting observed highfrequency (frequencies above 0.1 cycle min −1 , i.e., periods below ≈ 10 min) oscillations in thermocline regions of stratified lakes. Thorpe et al (1996) discussed internal waves with periods of between 6 and 10 min which they observed in Lake Geneva within a few hours after the passing of a disturbance that caused a rapid jump in the thermocline depth. The authors proposed three possible sources of these oscillations: (1) a soliton packet following the jump, (2) waves generated as the jump passed over or around rough topography, and (3) a moving disturbance produced by a thermocline jump near the shoreline accompanied by a region of high shear, low Richardson number, and a wake-like pattern of radiating internal waves.…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies reporting observed highfrequency (frequencies above 0.1 cycle min −1 , i.e., periods below ≈ 10 min) oscillations in thermocline regions of stratified lakes. Thorpe et al (1996) discussed internal waves with periods of between 6 and 10 min which they observed in Lake Geneva within a few hours after the passing of a disturbance that caused a rapid jump in the thermocline depth. The authors proposed three possible sources of these oscillations: (1) a soliton packet following the jump, (2) waves generated as the jump passed over or around rough topography, and (3) a moving disturbance produced by a thermocline jump near the shoreline accompanied by a region of high shear, low Richardson number, and a wake-like pattern of radiating internal waves.…”
Section: Introductionmentioning
confidence: 99%
“…Meinikmann et al (2015) observed that both the intensity of the contamination and its proximity to the lake inhibit nutrient retention within vadose zone and aquifer and allow significant phosphorus loads to be discharged into the lake. Tecklenburg and Blume (2017) found that large-scale LGD patterns were correlated with topography and groundwater flow field, whereas small-scale patterns correlated with grain size distributions of the lake sediment. However, the influence of geological conditions on spatial differences in LGD and associated nutrients input have not been well understood.…”
Section: Introductionmentioning
confidence: 92%
“…LGD and associated nutrients input are often characterized by large spatial variability due to the heterogeneity of geomorphy, surface hydrology, lakebed sediment lithology, hydrogeology, nutrient concentration levels of groundwater around lakes, etc (Wallace et al, 2020;Tecklenburg and Blume, 2017;Hare et al, 2017;Rosenberry et al, 2015;Meinikmann et al, 2015Meinikmann et al, , 2013Blume et al, 2013;Schneider et al, 2005). For example, Schmidt et al (2010) found that LGD rates were related to the drainage area/lake area ratio which promotes greater surface connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Although various methods of quantifying LGD exist (Tecklenburg and Blume;Dimova et al, 2015;Lewandowski et al, 2013;Stets et al, 2010), radioactive 222 Rn tracing has been widely and effectively used in recent years (Wallace et al, 2021(Wallace et al, , 2020Dabrowski et al, 2020;Hare et al, 2017;Petermann et al, 2018;Liao et al, 2018;Luo et al, 2018Luo et al, , 2016Luo et al, , 2014Burnett et al, 2017;Dimova et al, 2015Dimova et al, , 2013Gilfedder et al, 2015;Peterson et al, 2010;Schmidt et al, 2010Schmidt et al, , 2009. 222 Rn is a subset of 226 Ra and is widely present in inland rocks and water bodies.…”
Section: Introductionmentioning
confidence: 99%